Downward Longwave Irradiance at the Thule High Arctic Atmospheric Observatory (THAAO_DLI) - Meloni, Daniela; Di Sarra, Alcide; Di Iorio, Tatiana; Pace, Giandomenico; Muscari, Giovanni; Iaccarino, Antonio; Calì Quaglia, Filippo (2022)
Downward Longwave Irradiance at the Thule High Arctic Atmospheric Observatory (THAAO_DLI)